2002
DOI: 10.1177/0734904102020006470
|View full text |Cite
|
Sign up to set email alerts
|

Fire Retardant Effect of 2-methyl-1,2-oxaphospholan-5-one 2-oxide in the PPO/HIPS Blend

Abstract: A phosphorus-rich compound 2-methyl-1,2-oxaphospholan-5-one 2-oxide (OP) (Clariant, Germany), and poly(2,6-dimethylphenylene oxide) (PPO) were mixed with high impact polystyrene (HIPS). The combustion behavior of the formulations was studied by limiting oxygen index (LOI) and Underwriters Laboratories UL94 test. The mechanism of the fire-retardant action of the additives was studied by thermogravimetry, IR characterization of the solid residues and high boiling degradation products (HBPs) and GC/MS characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…2‐Methyl‐2,5‐dioxo‐1‐oxa‐2‐phospholane is a very potent flame retardant, because it gives a V‐0 rating at only 5 wt% loading in combination with 20 wt% PPO147 and its loading can be decreased to only 1 wt% when combined with triphenyl phosphate, but in this case 35 wt% PPO is needed 148. Balabanovich and co‐workers studied the mechanism of flame‐retardant action of 44 in combination with PPO,149 or novolac,150 or melamine150 or ammonium polyphosphate 151. It was shown that 44 does not increase the charring of PPO or novolac, so its main contribution seems to be the gas‐phase activity.…”
Section: Phosphorus‐based Flame Retardantsmentioning
confidence: 99%
“…2‐Methyl‐2,5‐dioxo‐1‐oxa‐2‐phospholane is a very potent flame retardant, because it gives a V‐0 rating at only 5 wt% loading in combination with 20 wt% PPO147 and its loading can be decreased to only 1 wt% when combined with triphenyl phosphate, but in this case 35 wt% PPO is needed 148. Balabanovich and co‐workers studied the mechanism of flame‐retardant action of 44 in combination with PPO,149 or novolac,150 or melamine150 or ammonium polyphosphate 151. It was shown that 44 does not increase the charring of PPO or novolac, so its main contribution seems to be the gas‐phase activity.…”
Section: Phosphorus‐based Flame Retardantsmentioning
confidence: 99%
“…The calculated data was composed by combining the TGA data of the components comprising of the mixture. [29][30][31] The results obtained are presented in Figure 4. The amounts of charred residues experimentally observed are higher than those values calculated for both phosphinate and phosphonate containing mixtures all over the temperatures whilst the opposite results are observed at lower degradation temperatures for phosphate containing mixture.…”
Section: Resultsmentioning
confidence: 89%
“…The materials have similar average heat of combustion (Table IV), with the ABS sample slightly lower. A cocharring polymer (polyphenylene oxide) which is commonly added to phosphorus-containing styrenic FR systems may also be playing a role [33][34][35].…”
Section: Resultsmentioning
confidence: 99%